Acute injuries in male elite and amateur mountain bikers: Results of a survey - Stoop, R.; Hohenauer, E.; Vetsch, T.; Deliens, T.; Clijsen, R. (Journal of Sports Science & Medicine, 2019)
Together with the growing popularity of mountain biking, the number of riders at risk for an acute injury has increased. A cross-sectional observational study was performed to describe the prevalence of acute injuries among elite and amateur riders and to determine predictive factors leading to a severe injury. A retrospective questionnaire was created comprising questions aiming on demographics, training volume, injury events and wearing of protective gear items. The survey was conducted during the Swiss Epic Mountain Bike Event in 2017. Complete data sets of male mountain bikers were used to determine prevalence. To evaluate injury related factors, only data sets reporting one or more injuries were included in the final analysis. Ninety-nine questionnaires were included to calculate the injury prevalence of 74% for elites and 69% for amateurs (p = 0.607). For the analysis of injury related factors 56 questionnaires were processed. Elites were significantly younger (p = 0.004) and had a significantly higher exposure time per year as amateurs (p < 0.001). The groups did not differ in number of injuries (p = 0.437) and number of severe injuries (p = 0.225). No predictive factors for a severe injury event were found. Both groups wore an equal amount of protective gear items (p = 0.846). A significant medium, respectively small correlation was found in both groups for mean hours of training per week and number of races per year (elites: r = 0.597, p = 0.023; amateurs: r = 0.428, p = 0.005). An equal prevalence of acute injuries was found in elite and amateur mountain bikers. Elites are at higher risk for an injury event due to their exposure time but do not suffer more or more severe injuries than amateurs.